Limiting nutrients of oyster pond seawater in the Marennes-Oleron region for Haslea ostrearia : applications to the mass production of the diatom in mesocosom experiments - Turpin, Vincent; Robert, Jean-michel; Goulletquer, Philippe (EDP Sciences, 1999)
Bioassays were carried out with the 'blue diatom' Haslea ostrearia Simonsen, which is responsible for oyster greening during the fattening period of Crassostrea gigas Thunberg in oyster ponds. Samples of seawater were taken from two oyster ponds: one without oysters and the other with 20 oysters per m_, maximal density allowed by the French AFNOR norm for 'refinement'. The aims were to clarify the nutrient requirements of this diatom, also to elucidate the eventual influence of C. gigas at this density on the seawater fertility and to envisage the mass production of this diatom by pond fertilization. Examination of cell numeric densities at the end of bioassays allows us to conclude that silicate was the first limiting nutrient, closely followed by phosphate. Chlorophyll a concentrations led to different conclusions: phosphate was the first limiting factor, but after the seawater storage period in ponds, seawater quality evolved to a deficiency of nitrogen. Silicate addition increased cell division rate, and silicate depletion increased chl a synthesis for this species. Examination of nutrient assimilation ratios confirms that H. ostrearia requires a large amount of silicon. From these results, it was possible to prepare a N + P + Si simplified medium which has been tested in laboratory and field mesocosm conditions. In both conditions, similar results were observed: a significant increase in H. ostrearia cell concentrations and consequently an evolution up to the greening stage. Applications of this work are numerous; the principal permits us to envisage the production of this species in 25-m3 ponds, with the aim of allowing constant production of the greening phenomenon. Des bioessais ont été réalisés avec la « navicule bleue » Haslea ostrearia Simonsen, qui est responsable du verdissement des huîtres durant la période d'affinage de Crassostrea gigas Thunberg dans les claires. Des échantillons d'eau de mer ont été prélevés dans deux claires : une sans huîtres et l'autre avec 20 individus au m2, densité ...